ANALISIS PENGELOLAAN DAN KINERJA BADAN USAHA MILIK DESA - Avisenna Harkat; Mohammad Luthfil Amin; Amalia Dwi Agustina; Bisma Januar Firmansah; Siti Aisyah (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This study aims to determine the management of BUMDes Mandiri and the success factors for the performance of BUMDes Mandiri in Suci Village, Panti District, Jember Regency. The research method used is descriptive qualitative. The type of data needed is primary data with data collection techniques by observation, interviews with BUMDes Mandiri administrators and documentation. The results showed that the main business activity of BUMDes Mandiri was selling household goods with cash and credit payments with a marketing strategy that was by utilizing the existing village apparatus and routine recitation activities for mothers. There are still no competitors in the Suci village, making it easier for BUMDes Mandiri to carry out their business activities. Independent BUMDes employees still need assistance from the sub-district in completing BUMDes financial reports. BUMDes Mandiri in 2021 will only compile a bank subsidiary ledger, general cash book, and cash subsidiary ledger